FINANCIAL AND SOCIAL EFFICIENCY ON INDONESIAN ISLAMIC BANKS: A NON-PARAMETRIC APPROACH - Aam Slamet Rusydiana; Lina Marlina (Bank Indonesia, 2019)
This paper explores financial and social efficiency in one assessment framework. In order to measure efficiency level of Islamic Banking Industry, this study uses Data Envelopment Analysis (DEA) and Free Disposal Hull (FDH) methods. The results show that the level of financial efficiency of Islamic banks in Indonesia from 2013 to 2018 tends to decrease. On the contrary, the level of social efficiency of Islamic banks in Indonesia has a tendency to increase. Furthermore, the value of social efficiency of Islamic banks in Indonesia was relatively lower compared to the value of financial efficiency. Within the Financial-Social Efficiency Quadrant framework, the study classified two Islamic banks in quadrant 1, three in quadrant 2, two in quadrant 3, and four in quadrant 4. It is imperative for Islamic banks that are in the low level of ‘social efficiency’ to develop a policy to keep in line with the five factors of maqashid sharia apart of maintaining efficiency in order to reach maslahah. For the regulators, the social efficiency measurement framework could be an alternative in considering Islamic bank performance beyond financial efficiency.